Diversity and distribution of Porifera on the Algerian coast (West Mediterranean) - Abdelali, Nerdjes; Grimes, Samir (Zootaxa, 2024)
The phylum Porifera has received limited attention in research studies along the Algerian coast. This study aims to compile a comprehensive inventory of Porifera species along the Algerian coast, spanning from the earliest documented work by Schmidt (1868) to the present day. The investigation meticulously catalogues a total of 136 species along the Algerian coast, distributed across 47 families, 18 orders, and 4 classes. This compilation includes 7 species endemic of Algerian waters, one invasive species, and 11 species protected by the Bern and Barcelona Conventions. Notably, the addition of 43 new species records enhances the original lists established by Schmidt and Topsent. Furthermore, this study presents a detailed analysis of the geographic distribution of these species, providing valuable insights into the biodiversity of the marine ecosystem in this region.